Bioprocess optimization for lactic and succinic acid production from a pulp and paper industry side stream - Olszewska-Widdrat, Agata; Xiros, Charilaos; Wallenius, Anders; Schneider, Roland; Rios da Costa Pereira, Laís Portugal; Venus, Joachim (Frontiers in Bioengineering and Biotechnology, 2023)
The effective and cheap production of platform chemicals is a crucial step towards the transition to a bio-based economy. In this work, biotechnological methods using sustainable, cheap, and readily available raw materials bring bio-economy and industrial microbiology together: Microbial production of two platform chemicals is demonstrated (lactic (LA) and succinic acid (SA)) from a non-expensive side stream of pulp and paper industry (fibre sludge) proposing a sustainable way to valorize it towards economically important monomers for bioplastics formation. This work showed a promising new route for their microbial production which can pave the way for new market expectations within the circular economy principles. Fibre sludge was enzymatically hydrolysed for 72 h to generate a glucose rich hydrolysate (100g·L-1 glucose content) to serve as fermentation medium for Bacillus coagulans A 541, A162 strains and Actinobacillus succinogenis B1, as well as Basfia succiniciproducens B2. All microorganisms were investigated in batch fermentations, showing the ability to produce either LA or SA, respectively. The highest yield and productivities for LA production were 0.99 g·g-1 and 3.75 g·L-1·h-1 whereas the SA production stabilized at 0.77 g·g-1 and 1.16 g·L-1·h-1.